Measuring the optimal government size that contribute to economic growth of the Muslim countries - Duasa, Jarita (2015)
The issue of a correct ‘government size’ for economic prosperity of a nation, particularly Muslim nation, is highly linked with the issue of optimal ‘role of state’. The present study attempts to utilise more efficient econometric methods on a sample of Muslim countries over a specific period of time in order to investigate relationship between government size and economic growth. It also attempts to identify optimal size of government (role of state) that maximise the economic growth of the countries by applying static and dynamic panel estimations on a widely used ‘growth model’ for assessing the impact of government size on economic growth. The findings indicate that small size of government contributes more on the economic growth of the countries. The results seem to be more robust by using fixed-effects model as compared to other static or even dynamic models.